Advancing socio-grammatical variation and change in honour of Jenny Cheshire - Beaman, Karen V.; Buchstaller, Isabelle; Fox, Sue; Walker, James A. (Routledge, Taylor & Francis Group, 2020)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- List of Figures -- List of Tables -- List of Contributors -- Foreword -- Acknowledgements -- Introduction: Advancing Socio-grammatical Variation and Change: Theoretical and Methodological Implications -- Section 1 Conceptualising Social Meaning -- 1.1 Historical and Ideological Dimensions of Grammatical Variation and Change -- 1.2 Towards an Integrated Model of Perception: Linguistic Architecture and the Dynamics of Sociolinguistic Cognition -- 1.3 Prestige Factors in Contact-Induced Grammatical Change -- 1.4 The Role of Syntax in the Study of Sociolinguistic Meaning: Evidence from an Analysis of Right Dislocation -- Section 2 Combining the Social and the Grammatical -- 2.1 What Happened to Those Relatives from East Anglia? A Multilocality Analysis of Dialect Levelling in the Relative Marker System -- 2.2 Restrictions on Relative Clauses in Auckland, New Zealand -- 2.3 Swabian Relatives: Variation in the Use of the wo-relativiser -- 2.4 Modelling Socio-grammatical Variation: Plural Existentials in Toronto English -- Section 3 Formal Approaches to Syntactic Variation -- 3.1 A Socio-grammatical Analysis of Linguistic Gaps and Transitional Forms -- 3.2 Variation and Change in the Particle Verb Alternation across English Dialects -- 3.3 Explaining Variability in Negative Concord: A Socio-Syntactic Analysis -- Section 4 Language Contact and Multiethnolects -- 4.1 Tracing the Origins of an Urban Youth Vernacular: Founder Effects, Frequency, and Culture in the Emergence of Multicultural London English -- 4.2 Bare Nouns in Prepositional Phrases in Cité Duits, a Moribund Miners' Multiethnolect (and Other Varieties of Dutch and German) -- 4.3 When Contact Does Not Matter: The Robust Nature of Vernacular Universals
Keywords: Sprachvariante; Variationslinguistik; Grammatik; Soziolinguistik; Festschrift